APLIKASI REAKTOR HIGH RATE PERFORMANCE PADA PENGOLAHAN LIMBAH CAIR INDUSTRI KECIL TAHU = Application of High Rate Performance Rector for Wastewater Treatment in Tofu Small Scale Industries - Parlina, Iin; Widodo, Lestari (Jurnal Teknologi Lingkungan, 2013)
Along with the development of biogas and its utilization, biogas reactors also evolved from conventional reactor types to high rate performance reactors, adapts to the needs of increased efficiency and also the characteristics of organic waste that is difficult if processed using ordinary reactor. However, this type of reactor basically has 3 types, namely fixed bed (packed-bed, anaerobic filters, fixed-film), fluidized bed reactor, and UASB/ Upflow Anaerobic Sludge Blanket reactor. From these high rate performance reactors, fixed bed reactor is the type that is pretty much developed and implemented in Indonesia, especially for treating organic wastewater from small industries, for example tofu, tapioca and slaughterhouses. Implementation of fixed bed reactor for the tofu industry until today has reached as much as 5 units that serve the needs of about 132 households in Banyumas District, Central Java Province. The fixed bed reactor’s performance is quite high if it is evaluated from biogas yield and the efficiency of the organic content in tofu industry’s wastewater. Implementation, dissemination, and replication of this reactor for treatment of other types of organic waste or other areas have the potential to support government programs in GHG mitigation actions, renewable energy sources provision, environmental protection and the development of energy self-sufficient villages.Keywords : biogas reactor - performance high - rate, fixed bed reactors, tofu industryAbstrakSeiring dengan perkembangan biogas beserta pemanfaatannya, reaktor biogas juga berkembang dari jenis reaktor konvensional hingga reaktor berunjuk kerja tinggi (high rate performance) menyesuaikan dengan kebutuhan peningkatan efisiensi dan juga karakteristik limbah organik yang sulit jika diolah dengan menggunakan reaktor biogas biasa. Namun, pada dasarnya reaktor ini memiliki 3 jenis, yaitu reaktor unggun tetap (fixed bed, packed-bed, anaerobic filter, fixed-film), reaktor unggun terfluidisasi (fluidized bed reactor), dan reaktor UASB (Upflow Anaerobic Sludge Blanket). Dari ketiga jenis reaktor berunjuk kerja tinggi tersebut, reaktor jenis unggun tetap adalah jenis yang cukup banyak dikembangkan dan diimplementasikan di Indonesia, terutama untuk mengolah limbah cair organik yang berasal dari industri kecil, misalnya tahu, tapioka dan rumah potong hewan. Implementasi reaktor unggun tetap untuk industri tahu hingga saat ini telah mencapai jumlah 5 unit reaktor yang melayani kebutuhan sekitar 132 Rumah tangga di Kabupaten Banyumas secara berkelanjutan. Kinerja reaktor unggun tetap ini dapat dikatakan cukup tinggi jika dinilai dari perolehan biogas dan efisiensi penurunan kandungan organic dalam limbah cair tahu. Program implementasi, diseminasi, dan replikasi reaktor ini untuk pengolahan jenis limbah organik yang lain atau daerah lain memiliki potensi dalam mendukung program pemerintah dalam aksi mitigasi Gas Rumah Kaca, penyediaan sumber energi terbarukan, perlindungan lingkungan dan pengembangan desa mandiri energi.Kata kunci : biogas, reaktor high-rate-performance, reaktor fixed bed, industri tahu